Tracking your book: What authors should know about Altmetrics - Montgomery, Lucy (-, 2013)
This presentation provides a brief introduction to altmetrics and discusses the challenges (and opportunities) associated with the emergence of altmetrics for books. It considers the pros and cons of altmetrics with a particular focus on open access scholarly books.